2007
DOI: 10.1002/iroh.200610865
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of Species Composition Patterns among Microcrustaceans, Rotifers and Testate Amoebae in a Shallow Pond

Abstract: In this study, spatial concordance among microcrustaceans, rotifers and testate amoebae was examined in a small pond in Central Brazil. The main goal was to test how consistently different taxonomic groups ordinate 9 sites distributed along the pond's main axis. Microcrustaceans were more abundant during the dry season, characterized by waters with high transparency and dissolved oxygen concentration. An increase in species richness and densities of rotifers and testate amoebae was detected during rainy season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 27 publications
3
24
0
2
Order By: Relevance
“…This was the case in Barra Bonita reservoir, the uppermost in the reservoir cascade along the Tietê River basin (Matsumura- . Its water level is fully controlled in order to regulate the levels in the downstream reservoirs, as well as the amount of hydroeletricity produced, one of the main zooplankton communities modifiers (Bini et al 2007). A similar situation was observed in the Jaguari and Jacareí reservoirs in the present study, where, during the dry season, the reservoirs levels were high, reaching 73.81% of their maximum capacity, whereas in the rainy season they were only 59.19% full.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This was the case in Barra Bonita reservoir, the uppermost in the reservoir cascade along the Tietê River basin (Matsumura- . Its water level is fully controlled in order to regulate the levels in the downstream reservoirs, as well as the amount of hydroeletricity produced, one of the main zooplankton communities modifiers (Bini et al 2007). A similar situation was observed in the Jaguari and Jacareí reservoirs in the present study, where, during the dry season, the reservoirs levels were high, reaching 73.81% of their maximum capacity, whereas in the rainy season they were only 59.19% full.…”
Section: Discussionsupporting
confidence: 82%
“…Besides recording biomass as a quantitative parameter, another community property used to indicate the trophic condition of the water body is the set of ratios between component populations of the zooplankton (rotifers, copepods and cladocerans) given that these ratios are also affected by eutrophication (Sampaio et al 2002, Sendacz et al 2006, Bini et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal rainfall is a major determinant of changes in several environmental variables in freshwater ecosystems in Brazilian Cerrado, for example, pH, water temperature (Melo and Froehlich, 2001;Bini et al, 2007), turbidity, conductivity, water flow, and discharge can be affected by rain. During our study an unusual period of drought in December caused by delay of rainfall, reflected in low variation in some environmental variables.…”
Section: Discussionmentioning
confidence: 99%
“…The major goal in ecology is to understand how parameters of biological communities (abundance, richness, and composition) respond to environmental variations (De Chaine and Martin, 2005;Bini et al, 2007). Studies on organism's distributions in nature have revealed recurring patterns along environmental gradients, such as changes in community structures and species composition; latitudinal congruence of diversity can arise even in unrelated groups from all biogeographical regions around the world (Heino, 2002;Bini et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation